Identification of tomato (Solanum lycopersicum) genotype for organic cultivation and better shelf life under North Indian plain condition - YADAV, RENU; VERMA, S B; RAMAWAT, NALEENI; YADAV, R K; ASKI, M; KUMAR, RAJENDRA (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was laid out in RBD having three replications to investigate the morphological performance, yield and shelf life of five different tomato (Solanum lycopersicum L.) varieties under organic and inorganic ambient. The different tomato varieties behaved significantly different from each other for various growth parameters. The organic ambient grown tomato var. Angoorlata gave the highest plant height, number of branches, leaves and flowers; the variety Pusa Sheetal recorded highest fruit length, fruit diameter, fruit shelf life and fruit yield. The var. Pusa Sheetal also grown inorganic ambient gave highest performance for number of fruits, fruit diameter, fruit weight, shelf life at room temperature and yield production. The potential of the variety Pusa Sheetal for accumulation of higher concentration of soluble solids such as sugars, Vitamin C, polyphenols and best performance for yield contributing attributes as well as highest shelf life at refrigerated condition in organic ambience reflects that it is an eco-health friendly genotype for organic tomato and longer shelf life. This novel finding reported for the first time for the variety Pusa Sheetal opens a new avenue for its larger scientific and practical utility for breeding of new genotypes suitable for organic farming with enhanced shelf life to meet out the increasing fondness and requirement of future consumers.